Dietary patterns and exposure to non-persistent endocrine-disrupting chemicals during pregnancy - Sarah Warkentin; Sandra Márquez; Hana Vespalcová; Bethany Knox; Mireia Gascon; Nuria Güil-Oumrait; Sandra González-Palacios; Maria Dolores Gomez Roig; Camille Lassale; Elisa Llurba; Matthieu Rolland; Amrit K. Sakhi; et al. (Environment International)
Background: Exposure to non-persistent endocrine disrupting chemicals (EDCs) is widespread, causing various adverse health effects, especially during pregnancy. Diet is a major source of EDCs and the identification of dietary patterns that give rise to higher exposure levels is crucial. We aimed to explore the relationship between dietary patterns during pregnancy and exposure to non-persistent EDCs. Methods: We included 640 pregnant women from the Barcelona Life Study Cohort (BiSC), Spain. Using food frequency questionnaires (2nd trimester), we estimated ultraprocessed food (UPF) consumption and Mediterranean diet adherence, and derived data-driven dietary patterns. Metabolites of phthalates, 1,2-cyclohexane dicarboxylic acid di(isononyl) ester (DINCH), chlorpyrifos and pyrethroid, polycyclic aromatic hydrocarbons (PAHs, including phenanthrenes), and organophosphates, and parent compounds of phenols and parabens were measured in weekly urine pools (3rd trimester). Associations between dietary patterns and EDCs were evaluated through multivariable linear regressions. Results: Higher compliance with a “Vegetarian” pattern or the Mediterranean diet was associated with lower levels of some of the phthalate metabolites (e.g., di-iso-nonyl phthalates [Geometric mean ratio (GMR) per unit increases in the “Vegetarian” score = 0.97, 95 %CI 0.95, 1.00]). Conversely, “Western” and “Animal protein” patterns, and UPF intake were associated with higher PAHs (e.g., “Western” and 2-Hydroxynaphthalene [GMR(95 %CI) 1.07(1.01, 1.13)]), pesticides (e.g., “Animal protein” and 3-Phenoxybenzoic acid [1.15(1.01, 1.32]), and phthalates metabolites levels (e.g., UPF and Monoethyl phthalate [1.05(1.01, 1.09)]). No association remained significant after correcting for multiple testing. Conclusions: Following a plant-based diet may help reduce the exposure to certain phthalate and organophosphate metabolites, whereas higher consumption of foods from animal origin and high in fat/sugar/salt may increase exposure to PAHs, pesticides, and phthalates metabolites in pregnancy.